Genetic Admixture History and Forensic Characteristics of Guizhou Sui People Inferred From Autosomal Insertion/Deletion and Genome-Wide Single-Nucleotide Polymorphisms - Yang, Meiqing; Yang, Xiaomin; Ren, Zheng; He, Guanglin; Zhang, Han; Wang, Qiyang; Liu, Yubo; Zhang, Hongling; Ji, Jingyan; Chen, Jing; Guo, Jianxin; Huang, Jiang; et al. (Frontiers in Ecology and Evolution, 2022)
Insertion-deletion (Indel) serves as one of the important markers in forensic personal identification and parentage testing, especially for cases with degraded samples. However, the genetic diversity and forensic features in ethnolinguistically diverse southwestern Chinese populations remain to be explored. Sui, one Tai-Kadai-speaking population residing in Guizhou, has a complex genetic history based on linguistic, historic, and anthropologic evidence. Here, we genotyped 30 Indels from 511 Guizhou Sui individuals and obtained around 700,000 genome-wide single-nucleotide polymorphisms (SNPs) in 15 representative Sui individuals to comprehensively characterize the genetic diversity, forensic characteristics as well as genomic landscape of Guizhou Sui people. The estimated forensic statistically allele frequency spectrum and parameters demonstrated that this Indels panel was polymorphic and informative in Tai-Kadai populations in southern China. Results of PCA, STRUCTURE, and phylogenetic trees showed that Guizhou Sui had a close genetic relationship with geographically close Tai-Kadai and Hmong-Mien people. Furthermore, genomic analysis based on the Fst and f4-statistics further suggested the genetic affinity within southern Chinese Tai-Kadai-speaking populations and a close relationship with geographically adjoining Guizhou populations. Admixture models based on the ADMIXTURE, f4, three-way qpAdm, and ALDER results demonstrated the interaction between the common ancestor for Tai-Kadai/Austronesian, Hmong-Mien, and Austroasiatic speaking populations played a significant role in the formation of modern Tai-Kadai people. We observed a sex-biased influence in Sui people by finding the dominant Y chromosomal type was a Hmong-Mien specific lineage O2a2a1a2a1a2-N5 but the mtDNA lineages were commonly found in Tai-Kadai populations. The additional southward expansion of millet farmers in the Yellow River Basin has impacted the gene pool of southern populations including Tai-Kadai. The whole-genome sequencing in the future will shed more light on the finer genetic profile of Guizhou populations.